Perancangan Storyboard Motion Graphic Edukasi Hidup Sehat Cegah Obesitas Anak bagi Generasi Milenial - Annisa Eka Puteri; Pungky Febi Arifianto; Mahimma Romadhona (FKIP, Universitas Palangka Raya, 2026)
Health is something greatly desired by everyone. In today's modern society, the lifestyle adopted tends to favor instant gratification because it's considered more practical, leading to a sense of laziness. This causes health issues, one of the urgent issues nowadays being obesity in children. The biggest cause of obesity in children is poor eating behavior and lack of physical activity practiced by parents, especially millennials. Therefore, this video motion is created to develop a storyboard used as a reference for educational motion graphics to motivate millennial parents to implement a healthy lifestyle for their children to prevent early obesity. The method used in this research is quantitative and qualitative with a qualitative descriptive approach. The data obtained is then developed to form a script that will be used as a reference in creating the storyboard. The result of the storyboard design will contain information on understanding obesity, factors supporting obesity in children, impacts, and prevention methods with practical guidance that can be directly applied in daily life through thumbnail, rough pass, and clean up stages. The storyboard design used as a reference for the educational motion graphic video is hopefully able to provide knowledge and information to millennial parents to care about their children's lifestyle to prevent early obesity.